The Social Protection for Persons with Disabilities during the COVID-19 Pandemic - Ratih Probosiwi; Kurnia Nur Fitriana (Indonesian Journal of Disability Studies, 2022)
To deal with the impact of the COVID-19 pandemic, the Indonesian government, including the Ministry of Social Affairs, has issued various social protection policies, including for persons with disabilities. In fact, people with disabilities still experience difficulties in accessing the program. This study aims to analyze these policies and the difficulties faced by persons with disabilities. This qualitative descriptive study found that people with disabilities had difficulty surviving during the pandemic. They lose their jobs because most of their work requires direct contact with other people. On the other hand, only a part of people with disabilities received social assistance because they were not recorded in the recipients of social assistance. The low ability to communicate risks to persons with disabilities is one of the reasons for the weak data collection of persons with disabilities. This study recommends more intense socialization and advocacy as well as equalizing perceptions about the concept of persons with disabilities and their needs.